2019
DOI: 10.1038/s41372-019-0497-4
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory outcomes of late preterm infants of mothers with early and late onset preeclampsia

Abstract: Objective To study the effect of early and late onset preeclampsia (EOPE, LOPE, respectively) on outcomes of late preterm infants. Study design Cohort study of late preterm infants admitted to a tertiary care NICU from January 2014-July 2015. Outcomes of late preterm infants of EOPE mothers were compared with the next late preterm infant of a LOPE mother and the next two late preterm infants of normotensive non-PE mothers. Primary outcome comprised use of continuous positive airway pressure, mechanical ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…According to the present findings, neonates of preeclamptic mothers had respiratory distress 2.6 times more than neonates of non-preeclamptic mothers. Consistent with the present study, previous studies have also shown that neonates of preeclamptic mothers more commonly suffer from respiratory distress syndrome (25)(26)(27). However, conflicting findings on the effect of preeclampsia on respiratory distress syndrome have been reported (14,28).…”
Section: Discussionsupporting
confidence: 91%
“…According to the present findings, neonates of preeclamptic mothers had respiratory distress 2.6 times more than neonates of non-preeclamptic mothers. Consistent with the present study, previous studies have also shown that neonates of preeclamptic mothers more commonly suffer from respiratory distress syndrome (25)(26)(27). However, conflicting findings on the effect of preeclampsia on respiratory distress syndrome have been reported (14,28).…”
Section: Discussionsupporting
confidence: 91%
“…There are many papers discussing the effects of preeclampsia on infants’ birth status and its impact on the occurrence of various preterm birth complications that develop in the neonate during hospitalization in a neonatal care unit [ 10 , 11 , 12 , 13 ]. First of all, it should be remembered that compared with children born to healthy mothers, these infants more often demonstrate complications such as body weight below the 10th percentile, neutropenia, thrombocytopenia, and complications typical of preterm births including infections, newborn respiratory distress syndrome, and the associated need for hospitalization in a neonatal intensive care unit, intraventricular hemorrhage, necrotizing enterocolitis, bronchopulmonary dysplasia, retinopathy of prematurity, or even death [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%